Theoretical Analysis of the Thermal Balance of Thermal Loss Accidents in Shilin, Yellow River, Gansu Province, and Ailao Mountain, Yunnan Province, in 2021 - Long Jia; Dong Ming; Su Huai (Redai dili)
Hypothermia is a type of safety accident that is often neglected in field activities. Its occurrence is not only a medical problem but also a thermodynamic problem and involves a specific geographical environment. An effective way to improve public awareness of hypothermia risk is to analyze hypothermia accidents from the perspective of heat transfer and heat balance between the human body and the environment. However, few reports have been written on relevant research. Therefore, this study uses the heat balance theory to build a calculation model of the clothing thermal resistance required by the human body to maintain a normal body temperature. The two most serious hypothermia death events in Shilin, Yellow River, Baiyin, Gansu province, and Ailao Mountain, Yunnan province, in 2021 are used as cases for analysis. The theoretical clothing thermal resistance has been calculated according to the external ambient temperature and human activity conditions (including metabolic rate and consumption coefficient) at the time of the event. By comparing the actual clothing thermal resistance value of the human body with the model, the theoretical clothing thermal resistance value has been calculated to study the hypothermia risk of the human body in the incident environment. The results show that, in the death incident of the Shilin Marathon on the Yellow River in Gansu Province, the theoretical thermal resistance of clothing required by the human body to maintain a normal body temperature was between 0.72 and 4.45 clo under different temperature conditions (resting, walking, and long-distance running), while the actual thermal resistance of the clothing worn by the accident personnel was 0.32 clo. The theoretical thermal resistance of the clothing is higher than that of the actual clothing, resulting in a high risk of temperature loss. Regarding the death event in the Ailao Mountain geological survey, the theoretical clothing thermal resistances required for the human body to maintain a normal body temperature under different temperatures while camping (sleeping), conducting field work, and mountaineering were 2.70-6.52 clo, 1.06-2.27 clo, and 0.55-1.75 clo, respectively. The actual thermal resistance of the clothing worn by the accident personnel was 1.86clo. During the accident, as long as the human body was in a climbing or working state, the difference between the theoretical and actual clothing thermal resistance was small, and the risk of hypothermia was low. However, while camping (sleeping), the theoretical clothing thermal resistance was higher than the actual clothing thermal resistance, and the lower the temperature, the greater the difference―especially at night when the temperature drops to its lowest point. At that point, the theoretical clothing thermal resistance could have been more than 3.5 times higher than the actual clothing thermal resistance, posing a serious risk of hypothermia. The results show the inevitability of hypothermia deaths in Shilin of the Yellow River in Gansu Province and Ailao Mountain in Yunnan Province. The insufficient prediction of hypothermia risk was the main cause of the hypothermia accidents. The calculation model constructed in this study can predict and evaluate the hypothermic risk of a certain outdoor activity in the future, provide a theoretical basis and research paradigm of thermodynamics and environmental science for improving public awareness about hypothermic risk, and is an effective means to prevent hypothermic accidents. Some measures and suggestions are provided for geographers engaged in long-term field investigation to avoid field hypothermia.